Modelling the impact of fungal spore ice nuclei on clouds and precipitation - Petrus, Ana; id_orcid:0 000-0002-0928-8894; Lohmann, Ulrike; Storelvmo, Trude (IOP Publishing, 2013)
Some fungal spore species have been found in laboratory studies to be very efficient ice nuclei. However, their potential impact on clouds and precipitation is not well known and needs to be investigated. Fungal spores as a new aerosol species were introduced into the global climate model (GCM) ECHAM5-HAM. The inclusion of fungal spores acting as ice nuclei in a GCM leads to only minor changes in cloud formation and precipitation on a global level; however, changes in the liquid water path and ice water path as well as stratiform precipitation can be observed in the boreal regions where tundra and forests act as sources of fungal spores. Although fungal spores contribute to heterogeneous freezing, their impact is reduced by their low numbers as compared to other heterogeneous ice nuclei. ISSN:1748-9326 ISSN:1748-9318